Aggregate dependent risks - risk measure calculation - Heilpern, Stanisław (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2011)
We investigate the sum of dependent random variables. The dependent structure is modeled by copulas. The risk measures, VaR and ES of such sums, are calculated. We present the lower and upper border of VaR. The examples when the marginals have exponential and Pareto distribution are investigated. The influence of the degree of dependence on the value of VaR of the sum of dependent random variables is analysed.
Mathematical Economics, 2011, Nr 7 (14), s. 107-122
Keywords: Value at Risk; dependent random variables; copula; Frechet bounds; expected shortfall